Influence of tillage and fertilizer management practices on productivity and resource use efficiency of groundnut (Arachis hypogaea) in Thar Desert of Rajasthan - POONIA, TANUJA; KUMAWAT, S M; BHUNIA, S R; JOHRI, S K (The Indian Journal of Agricultural Sciences, 2022)
Conventional tillage practices in Thar Desert of Rajasthan are posing a serious threat of natural resource degradation due to soil erosion induced by high temperature and winds. A 2-year study was conducted to explore the efficient tillage and nutrient management practices evaluate the effects of these practices on groundnut crop performance and resource use efficiency. It consisted 18 treatment combinations; 3 tillage practices, viz. T1 - minimum tillage, T2 - deep tillage, and T3 - conventional tillage main plots; and six fertilizer management practices, viz. F0 - no fertilization, F1 -recommended dose of NK fertilizer, F2 - recommended dose of NPK fertilizer (RDF), F3 - RDF + PSB @2.5 kg/ha, F4 - F3+ AMF @2 kg/ha, and F5 - F3+ AMF @4 kg/ha as sub plots. The highest LAI, crop growth rate and relative growth rate was recorded with deep tillage (T2) and F5 treatment combination. Deep tillage (T2) produced significant at par yields (pod and haulm) with conventional tillage (2981 and 4878 kg/ha). Higher water use efficiency of 4.72% and 13.25% were recorded with T3 compared to T2 and T1, respectively. Fertilizer management practices F5 and F4 recorded significantly at par and higher yields (pod, kernel, haulm and biological) compared to other combinations. The F5 treatment notable increased 16.7% and 90.2% water and nutrient use efficiency over RDF (6.69 kg/ha mm and 14.95 kg/kg), respectively. In Thar Desert, deep tillage along with chemical fertilizers and bio-inoculants found best management practices in terms of productivity and resource use efficiency.